2016
DOI: 10.1002/admi.201500619
|View full text |Cite
|
Sign up to set email alerts
|

Electron Confinement at the Si/MoS2 Heterosheet Interface

Abstract: lead to a nontrivial electronic coupling at the Si/MoS 2 heterosheet (HS) interface with possible impact on the electronic and optical applications. Indeed, interfacing MoS 2 with conventional semiconductors recently has recently led to the realization of a subthermionic tunnel FET, [ 12 ] and it was proposed as a feasible avenue for an improved photodetection [ 13 ] and enhanced photoresponsive behavior. [ 14 ] In the present work, our aim is to unravel the electronic band line-up at the HS interface between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Particularly, TMDCs layers have been deposited on the Si surface by various approaches to develop heterojunction device for solar cells and photodiode applications . The MoS 2 ‐layered material‐based photoresponsive devices have shown great potential as they show high optical absorption in the visible spectrum, faster photoresponse, and relative ease of fabrication . Thus, the combination of n‐type MoS 2 with p‐type Si is of significant interest to develop a VdW heterojunction device .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, TMDCs layers have been deposited on the Si surface by various approaches to develop heterojunction device for solar cells and photodiode applications . The MoS 2 ‐layered material‐based photoresponsive devices have shown great potential as they show high optical absorption in the visible spectrum, faster photoresponse, and relative ease of fabrication . Thus, the combination of n‐type MoS 2 with p‐type Si is of significant interest to develop a VdW heterojunction device .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] The MoS 2 -layered material-based photoresponsive devices have shown great potential as they show high optical absorption in the visible spectrum, faster photoresponse, and relative ease of fabrication. [20][21][22][23][24] Thus, the combination of n-type MoS 2 with p-type Si is of significant interest to develop a VdW heterojunction device. [25][26][27] Salahuddin et al has reported the fabrication of heterojunction photodetectors with mechanically exfoliated MoS 2 flake on amorphous Si.…”
Section: Introductionmentioning
confidence: 99%
“…

more, as will be discussed in the following, the optical properties of the metallic layer at longer wavelengths strongly attenuates the photo-conversion.

A promising and widely investigated approach seems to be the exploitation of graphene. As recently reported by different groups, [26,27] a narrow band-gap (2D) semiconductor in intimate contact with a bulk silicon can induce a band-gap narrowing in the latter, leading to the shift of the band-edge absorption spectrum toward longer wavelengths. [21][22][23][24][25], as a possible solution to develop photodetectors able to work in the long-wavelength range.

In this paper, an infrared, lateral Schottky photo-diode based on a multilayer-graphene/intrinsic-silicon (MLG/i-Si) heterojunction is presented.

…”
mentioning
confidence: 89%
“…As recently reported by different groups, [26,27] a narrow band-gap (2D) semiconductor in intimate contact with a bulk silicon can induce a band-gap narrowing in the latter, leading to the shift of the band-edge absorption spectrum toward longer wavelengths. The junction shows a strong gain of the responsivity in the long wavelength region as compared to a standard metal/Si junction.…”
mentioning
confidence: 89%
“…As an emerging member of nanostructured materials, the 2D nanosheets of graphene and layered inorganic solids attract intense research interest because of their unique characteristics such as unusually high structural and morphological anisotropy, diverse physicochemical properties, and valuable functionalities. [1][2][3][4][5][6] While the synthesis of many other nanostructured materials heavily relies on crystal growth mechanism, the 2D nanosheet can be synthesized by soft-chemical exfoliation process of the pristine layered material. [6][7][8][9][10][11][12][13] Such an exfoliation process leads to the separation of layered crystal lattice into individual sheets with single domain.…”
Section: Introductionmentioning
confidence: 99%